Response of Peanut Plant Varieties (Arachys hypogaea L.) to Administering Biological Organic Fertilizer - Rosmiah Rosmiah; Iin Siti Aminah; Neni Marlina; Dasir dasir; Suyatno Suyatno; Ahmad Sofian; Okti Okti (Journal of Global Sustainable Agriculture, 2023)
Peanuts are a type of legume that is ranked second economically after soybeans. The decline in peanut production has received special attention from the government, which has made adjustments to the processing and use of superior varieties as well as the use of fertilizer. The research aims to study the response of several peanut varieties to doses of biological organic fertilizer. The research was carried out from December 2021 to March 2022 on farmers' land in Tanjung Steko Village, North Indralaya District, Ogan Ilir Regency, South Sumatra. The research used an experimental method with a split-plot design and three replications, so there were 27 plots. The main plot factor is the dose of biological fertilizer (P), which consists of: P 1 = 75 kg/ha; P 2 =100 kg/ha; and P 3 = 125 kg/ha. The subplot factor is the peanut plant variety (V), which consists of V1 = Garuda, V2 = Tuban, and V3 = Giraffe. Observation parameters are: plant height (cm); number of primary branches (branches); pod weight per plant (g); number of pods containing (pods); Number of empty pods (pods); Weight of 100 seeds (g); production per plot (kg). The research results showed that the three varieties had a high response to the application of biological fertilizer. The research results showed that plant growth was not significantly different, but there were differences in production. The interaction between the treatment doses of P3 biological organic fertilizer and V3 gave the best results, namely peanut production of 1.50 kg/plot or the equivalent of 2.00 tons/ha